Oxford Guide to Low Intensity CBT Interventions 2010
DOI: 10.1093/med:psych/9780199590117.003.0022
|View full text |Cite
|
Sign up to set email alerts
|

Treatment credibility and satisfaction with internet interventions

Abstract: Chapter 22 explores treatment credibility and satisfaction, and notes that users’ ratings of treatment credibility before the commencement of an online intervention tend to range from intermediate to high and are comparable with user ratings of satisfaction after use. The authors also note that, in some cases, user satisfaction might be higher for online treatments than for their face-to-face counterparts. They offer insights as to why ratings may vary and how LI practitioners might manage the variation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Mental health information can also increase treatment credibility, thereby motivating users to engage with a given treatment [ 208 ], and can provide evidence-based justifications for performing recommended activities (see the “Recommend Activities” section). Notably, users have a tendency to perceive health information on the Internet as being credible [ 209 ], so this raises the ethical imperative of ensuring that all information is strictly evidence based.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mental health information can also increase treatment credibility, thereby motivating users to engage with a given treatment [ 208 ], and can provide evidence-based justifications for performing recommended activities (see the “Recommend Activities” section). Notably, users have a tendency to perceive health information on the Internet as being credible [ 209 ], so this raises the ethical imperative of ensuring that all information is strictly evidence based.…”
Section: Resultsmentioning
confidence: 99%
“…The simplicity of a program’s interface and ease of navigation significantly influence user perceptions of quality in Web-based mental health interventions [ 264 , 265 ]. User satisfaction and perceptions of credibility directly influence engagement and therapeutic benefit [ 208 ]. Building an enjoyable app with good graphic design and a slick, intuitive, and satisfying interface is necessary for an effective intervention [ 5 , 266 ].…”
Section: Resultsmentioning
confidence: 99%
“…This was in spite of the fact that the patients were told otherwise. This might have compromised the patients expectancy of treatment effect of the iCBT and damaged the working alliance which might have compromised treatment outcome ( Waller and Gilbody, 2009 , Ritterband et al, 2010 , Preschl et al, 2011 ). Finally, the EQ-VAS is a one-item measurement scale.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are important as previous research has found the simplicity of a program's interface and ease of navigation positively impact user perceptions of quality in Web‐based mental health interventions (Kenardy et al, 2006; Kerr et al, 2006). In turn, high levels of satisfaction and perceptions of credibility are associated with increased engagement and therapeutic benefit (Ritterband et al, 2010).…”
Section: Discussionmentioning
confidence: 99%